Re-presenting China in Digital Immersive Art: Virtual Reality, Imaginaries, and Cultural Presence - Zhao, Xinyang (Curtin University, 2022)
The thesis explores how digital technology, in particular virtual reality and augmented reality, is playing a role in China’s rejuvenation, especially in relation to cultural displays, performances, and art exhibitions. This project examines how audiences, both in China and globally, respond to ‘Digital China’, a concept describing how people’s everyday lives in China are becoming superconnected by digital technology. Qualitative methodology with a multi-perspectival approach is applied to advance the aim of the project.